Tingkat Stres, Ansietas, dan Depresi Pada Mahasiswa Keperawatan Tahun Pertama Selama Pembelajaran Daring Dimasa Pandemi Covid-19 - Krismonica, Priskila; Palumpun, Erny; Lase, Etika; Paula, Veronica; Silitonga, Ester (Universitas Malahayati, 2024)
ABSTRACT Learning online in the COVID-19 Pandemic situation sure does make college students have to adapt with the situation, especially the first year students who have experienced the transition from Senior High School to the university. This change in learning methods has obstacles that prevent students from participating in an effective learning process. This can give pressure that causes anxiety, stress, and depression. This research aims to know the stress, anxiety, and depression levels of first-grade nursing students during online learning in the COVID-19 pandemic era. This research uses a descriptive quantitative method with convenience sampling technique to 379 nursing students in DKI Jakarta and Tangerang. The research instruments used are questioner DASS-21 (Depression Anxiety Stress scale) from Lovibond & Lovibond (1995) The result of the stress category shows that the number of nursing students who got normal stress was 257 respondents, 37 respondents were light stress, 47 respondents were moderate stress, 34 respondents were severely stressed, and 4 respondents were having very severe stress. In the anxiety category, the number of nursing students who got normal anxiety was 143 respondents, 43 respondents were light anxiety, 105 respondents were moderate anxiety, 37 respondents were severely anxious, and 51 respondents were very severe anxiety. In the depression category, the number of nursing students who got normal depression was 228 respondents, 55 respondents were light depression 51 respondents were moderate depression, 26 respondents were severely depressed and 19 respondents were very severe depression. This research can be concluded that first-year nursing students have different levels of stress, anxiety, and depression ranging from mild to very severe and experience signs and symptoms of stress, anxiety and depression. Keywords: Anxiety, COVID-19, Depression, Online Learning and Stress ABSTRAK Pembelajaran daring selama pandemi COVID-19 membuat mahasiswa harus beradaptasi, terlebih bagi mahasiswa tahun pertama yang mengalami transisi dari masa sekolah menengah atas menuju perguruan tinggi. Perubahan metode pembelajaran ini memiliki hambatan-hambatan yang menghalangi mahasiswa untuk mengikuti proses pembelajaran yang efektif. Hal ini memberi tekanan yang menimbulkan ansietas, stres dan depresi. Penelitian ini bertujuan untuk mengetahui gambaran tingkat stres, ansietas dan depresi pada mahasiswa keperawatan tahun pertama selama pembelajaran daring dimasa pandemi COVID-19. Penelitian ini menggunakan metode deskriptif kuantitatif dengan teknik convenience sampling kepada 379 mahasiswa keperawatan di DKI Jakarta dan Tangerang. Instrumen yang di gunakan pada penelitian ini adalah kuesioner DASS-21 (Depression Anxiety Stress Scale) oleh Lovibond & Lovibond (1995). Hasil penelitian pada kategori stres menunjukkan mahasiswa keperawatan mengalami stres normal sebanyak 257 responden,stres ringan 37 responden, stres sedang 47 responden, stres berat 34 responden dan sangat berat 4 responden. Pada kategori ansietas mahasiswa keperawatan mengalami ansietas normal sebanyak 143 responden, ansietas ringan 43 responden, ansietas sedang 105 responden, ansietas berat 37 responden dan ansietas sangat berat 51 responden. Pada kategori depresi mahasiswa keperawatan mengalami depresi normal sebanyak 228 responden, depresi ringan 55 responden, depresi sedang 51 responden dan depresi berat 26 responden dan sangat berat sebanyak 19 responden. Penelitian ini dapat di simpulkan bahwa mahasiswa keperawatan tahun pertama memiliki tingkat stres, ansietas, dan depresi yang berbeda-beda dimulai dari yang ringan hingga sangat berat serta mengalami tanda dan gejala baik stres, ansietas maupun depresi. Kata Kunci: Ansietas, COVID-19, Daring, Depresi, dan Stres